Violence in our country as a public health issue, prevalence of facial trauma at the hospital general de Mexico from 2020-2024 - Araujo Azcue, Arsenio Fernando; Renteria, Jorge Moises Morales; Chang, Emiliano Ortiz; Bonilla, Sandra Yetzel Hernandez; Lopez, Rodolfo Luciano Rios Lara Y.; Vitelly, Juan Antonio Ugalde (International Journal of Research in Medical Sciences, 2025)
Background: Facial trauma represents a significant pathology in emergency services. The facial skeleton is susceptible to injuries ranging from soft tissue wounds to complex fractures. The leading causes include motor vehicle accidents, assaults, and falls, with a higher incidence in men aged 20-30 years. Methods: A retrospective, observational, and descriptive study was conducted at the department of plastic and reconstructive surgery of the hospital General de México. Medical records from January 2020 to December 2024 were reviewed to collect data on gender, age, injury mechanisms, affected anatomical structures, and treatments. Ethical guidelines were strictly followed. Results: A total of 4218 cases of facial trauma were analyzed. Men constituted 87% of the patients, with a peak incidence in the third decade of life. Superficial soft tissue injuries accounted for 89.8% of cases, while 10.2% involved fractures. Mandibular fractures (14.7%) and orbital injuries (39.1%) were the most common. Assaults were the primary cause (62.2%), followed by motor vehicle accidents (14.7%) and blunt object impacts (9.8%). Open reduction and internal fixation were performed in 188 cases, while 226 cases were managed conservatively. Conclusions: The study underscores the high incidence of facial trauma in urban populations, with violence being the leading cause. The findings emphasize the need for targeted prevention strategies and individualized treatment approaches based on injury severity and etiology.